2011
DOI: 10.1071/py10012
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and physical activity guidance for women in the pre- and post-natal period: a continuing education needs assessment in primary health care

Abstract: The study objective was to assess primary health care (PHC) providers' exposure to women in the pre- and post-natal period, current nutrition and physical activity guidance practices, confidence and perceived needs for continuing education relevant to nutrition and physical activity guidance in the peri-natal period. A self-administered cross-sectional questionnaire survey amongst a purposively recruited sample of 226 local primary health care providers evenly distributed across general practice, community nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
3
16
0
2
Order By: Relevance
“…obstetricians, family medicine practitioners, and certified nurse midwives) attitudes, beliefs, perceived barriers and current practices related to antenatal physical activity in order to help inform the development of future intervention studies. Consistent with previous research, findings from the present study suggest that the majority of HCPs across all three specialties believe engagement in antenatal physical activity will result in improved health for mother and baby [18,20,21]. Moreover, most of the HCPs agree that it is important that pregnant women free of obstetric complications should meet the DHHS recommendations on antenatal physical activity.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…obstetricians, family medicine practitioners, and certified nurse midwives) attitudes, beliefs, perceived barriers and current practices related to antenatal physical activity in order to help inform the development of future intervention studies. Consistent with previous research, findings from the present study suggest that the majority of HCPs across all three specialties believe engagement in antenatal physical activity will result in improved health for mother and baby [18,20,21]. Moreover, most of the HCPs agree that it is important that pregnant women free of obstetric complications should meet the DHHS recommendations on antenatal physical activity.…”
Section: Discussionsupporting
confidence: 78%
“…Bauer et al (2004) surveyed 60 practicing physicians in Michigan and found that the majority believe exercise is beneficial and that they recommend exercise to their patients; however, it appears that not all are aware, or follow, current ACOG recommendations [18]. Recently Hughes et al 2011 surveyed HCPs in general practice, community nursing and pharmacy to determine continuing education needs related to perinatal physical activity counseling. Results suggested that the majority of providers agree that physical activity guidance is important and recommend that future continuing education efforts be tailored according to type of primary care training [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumers visit community pharmacies on a regular basis, with reports documenting that the average Australian visits a pharmacy up to 14 times a year [18]. More specifically, in Australia, pharmacy staff (pharmacists and pharmacy assistants) come into contact with women in the pre-pregnancy, pregnancy and post-partum stages more than any other primary health care professional, including general practitioners and nurses [19]. In the UK, consumer access to pharmacies and pharmacists is similar to Australia, with 60-80% of pharmacy consumers reported to be women [20].…”
Section: Introductionmentioning
confidence: 99%